Dynamic pH and Thermal Analysis of Paper-Based Microchip Electrophoresis - Muhammad Noman Hasan (MDPI AG, 2021)
Paper-based microchip electrophoresis has the potential to bring laboratory electrophoresis tests to the point of need. However, high electric potential and current values induce pH and temperature shifts, which may affect biomolecule electrophoretic mobility thus decrease test reproducibility and accuracy of paper-based microfluidic electrophoresis. We have previously developed a microchip electrophoresis system, HemeChip, which has the capability of providing low-cost, rapid, reproducible, and accurate point-of-care (POC) electrophoresis tests for hemoglobin analysis. Here, we report the methodologies we implemented for characterizing HemeChip system pH and temperature during the development process, including utilizing commercially available universal pH indicator and digital camera pH shift characterization, and infrared camera characterizing temperature shift characterization. The characterization results demonstrated that pH shifts up to 1.1 units, a pH gradient up to 0.11 units/mm, temperature shifts up to 40 °C, and a temperature gradient up to 0.5 °C/mm existed in the system. Finally, we report an acid pre-treatment of the separation media, a cellulose acetate paper, mitigated both pH and temperature shifts and provided a stable environment for reproducible HemeChip hemoglobin electrophoresis separation.